Pengaruh Literasi Ekonomi terhadap Perilaku Konsumtif Mahasiswa - Mukarramah Mukarramah; Inanna Inanna; Muhammad Hasan; M. Ihsan Said Ahmad; Nurdiana Nurdiana (Indonesian Journal of Social and Educational Studies, 2020)
This research aims to study the economic literacy of consumer behavior of students of the State University Makassar Economic Education Study. This research was categorized as a quantitative study with participants 350 students, while the sample was 78 students of the State University University Makassar Economic Education. Collection data is done by using the technique and questionnaire. Analysis technique used is descriptive analysis. The results showed that there was an effect of economic literacy on the consumptive behavior students of State University Makassar Economic Education Study.